2018
DOI: 10.1007/s12020-018-1644-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival of aggressive variants of papillary thyroid carcinoma in patients under 55 years old: a SEER population-based retrospective analysis

Abstract: In the age group <55 years, DSV and TCV are more likely to exhibit aggressive characteristics than CPTC. Patient <55 years of age with DSV have excellent survival likewise, while patients <55 years of age with TCV carry worse survival. Further investigation for the recurrence risk of patients <55 years with these variants would contribute to optimal clinical management making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
4
17
1
Order By: Relevance
“…In agreement with previously reported studies, patients were mainly women (10)(11)(12)(13)(14)(15)(16)(17)(18)19) and mean age was under 30s (range 10-65 years) (11,12,(16)(17)(18)(19)(20)(21).…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…In agreement with previously reported studies, patients were mainly women (10)(11)(12)(13)(14)(15)(16)(17)(18)19) and mean age was under 30s (range 10-65 years) (11,12,(16)(17)(18)(19)(20)(21).…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…Feng et al also found that not receiving surgery was a risk factor for PTC-specific mortality among patients younger than 55 years. Surgery might therefore be appropriate for PTC patients regardless of age [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SEER data set was initiated in 1973 as the main USA population-based cancer registry. This database contains data from many geographic regions and covers information on demographics, staging, treatments, and survival; however, certain specific clinical details are not available [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…1b). Recent meta-analysis still considers diffuse sclerosing variant as a high-risk PTC because of a high incidence of extrathyroid invasion at surgery, advanced tumor stage at presentation and bilaterality, however there is an obvious trend in the modern institutional series that diffuse sclerosing variant PTC has no adverse effect on survival [101][102][103][104][105] (Table 2).…”
Section: Diffuse Sclerosing Variant Ptcmentioning
confidence: 99%